Environmental education for sustainable development in engineering education in Colombia - Acosta-Castellanos, Pedro Mauricio; Queiruga-Dios, Araceli; Camargo-Mariño, Julian A. (Frontiers in Education, 2024)
Introduction Environmental education (EE) has been extensively studied and promoted in Latin America, particularly in Colombia, through educational policies and regulations at all educational stages. While EE is well-established, Education for Sustainable Development (ESD) is gaining increasing global importance, especially with the advent of the Sustainable Development Goals (SDGs). Despite this, there remains a lack of knowledge, application, and research of ESD within engineering programs in higher education. This study aims to explore these gaps and assess the acceptance of ESD compared to EE among engineering students in Colombia. Methods A survey was conducted among 406 engineering students from eight universities in Colombia that offer undergraduate engineering programs. The survey included both Likert scale questions and open-ended questions. The objective was to measure students’ knowledge and perception of ESD, identify the roots of EE within engineering programs, and evaluate the progressive integration of ESD in these curricula. Results The results revealed the deep-rooted presence of EE in Colombian engineering programs and a gradual incorporation of ESD into these curricula. However, significant gaps were identified. The majority of students demonstrated limited knowledge of ESD and Sustainable Development (SD). Furthermore, there was a noticeable lack of academic areas or subjects within the engineering curriculum that specifically promote the knowledge and application of ESD. Students’ responses also highlighted the unusual convergence between EE, a traditionally conservationist field, and ESD, which is more development-oriented. Discussion This research identifies several critical challenges faced by engineering education in Colombia. The limited awareness of ESD among students suggests a need for enhanced integration of sustainable development concepts within engineering curricula. The lack of academic subjects dedicated to ESD further exacerbates this issue. Based on these findings, a transition strategy is proposed to bridge the gap between EE and ESD in Colombian higher education. This strategy aims to provide a smoother transition and better integration of sustainable development principles within engineering programs, ultimately supporting the development of engineers equipped to address contemporary global challenges.